PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN (ENDURANCE) ATLET KARATE DOJO PRESTASI INDONESIA KARATE- DO (INKADO) KAB. SIAK - sinaga, Bandarudin Welman; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstark: The problem in this research is that when a race in the first round is still strong and fast, so that the first half of its performance is maximized, the endurance of the athlete decreases on arrival in the second round and his race performance drops, no more force appears when pedaling. If this condition is allowed to continue, it is difficult for the athlete to achieve maximum performance. The title of this study is